Money Laundering Crime in the Perspective of Islamic Law in the System of Proof - Ariman Sitompul; Arie Kartika; Windy Sri Wahyuni; Maswandi Maswandi (Justicia Islamica, 2022)
This paper initiates the study of Islamic law related to the reverse proof system contained in Articles 77 and 78 in law number 8 of 2010 concerning the Prevention and Eradication of The Criminal Action of Money Laundering. In this study, the authors used qualitative methods to respond to the concept of fiqh life in Indonesia. The purpose of this study is related to the burden of proof reversed using the opinions of Islamic law, usul fiqh, and legislation. From the study results, the evidence to the contrary does not apply to all criminal cases but only to exceptional cases such as money laundering. Money laundering in Indonesia can be in the form of enrichment by illegal means. Islamic law in the development of law in Indonesia also minimizes the crime of criminal origin that develops and continues in money crimes from the influence of controlling illicit money that feels like halal money and also includes sanctions against perpetrators of crimes punished by Islam into national law.